PENGARUH PASSIVE STRETCHING DAN ISTRUMENT ASSISTED SOFT TISSUE MOBILIZATION (IASTM) TERHADAP PENURUNAN NYERI OTOT PERSERTA LARI MARATHON - Alfian Noha Zulkarnain; Yerikho Surya Nugraha (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Sport is a form of physical activity that is structured, planned and sustainable by following certain rules which have the main objective of increasing physical fitness and achievement. Marathon sports is a type of sporting event that is much-loved and popular in the world, including Indonesia. Sports that have the characteristics of running with long distances has a high variability in the incidence of running-related injuries (RRIs). So researchers are interested in knowing the benefits of giving IASTM and passive stretching to marathon athletes. This study aims to add science on the management of athletes who experience muscle pain after running a marathon. This research method used quasy experimental with one group pretest-posttest design. The number of samples in this study were 24 athletes marathon grouped into one treatment group. The results of the study show the results of the sig. (2-tailed) pretest and post-test of 0.000 smaller compared with the value of α 0.05, so it can be concluded that the administration of IASTM and passive stretching has a significant effect on reducing muscle pain in marathon athletes. For further research, it is hoped that compared the treatment of muscle pain using IASTM and passive stretching with other methods, to determine the level of effectiveness and efficiency in treating muscle pain in marathon athletes